2013
DOI: 10.1038/pr.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk fatty acid profile in relation to infant growth and body composition: results from the INFAT study

Abstract: Background: There is some evidence that the n-6/n-3 long-chain polyunsaturated fatty acids (LCPUFAs) ratio in early nutrition, and thus in breast milk, could influence infant body composition. Methods:In an open-label randomized controlled trial (RCT), 208 healthy pregnant women were allocated to a dietary intervention (supplementation with 1,200 mg n-3 LCPUFAs per day and instructions to reduce arachidonic acid (AA) intake) from the 15th wk of gestation until 4 mo of lactation or to follow their habitual diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 34 publications
6
71
2
Order By: Relevance
“…Another study by Savastano et al (39) showed that subcutaneous body fat helps in insulating the body. Postnatal FM gain could be stimulated by breast-milk adiponectin and n-3 long-chain PUFAs, as supported by other studies (32,40). This FM gain could mediate the association of breast-milk FA and adiponectin concentrations with linear growth.…”
Section: Discussionsupporting
confidence: 72%
“…Another study by Savastano et al (39) showed that subcutaneous body fat helps in insulating the body. Postnatal FM gain could be stimulated by breast-milk adiponectin and n-3 long-chain PUFAs, as supported by other studies (32,40). This FM gain could mediate the association of breast-milk FA and adiponectin concentrations with linear growth.…”
Section: Discussionsupporting
confidence: 72%
“…Potential explanations for the discrepancy between our findings and previous studies include differences in the dose and type of n-3 LCPUFA supplied, the timing of the supplementation, the trial design, and the accuracy of measurements. The dose of n-3 LCPUFA in our trial was 2.4 g per day, which is higher than in most previous studies, in which 900 mg or 1.5 g was administered,792526 and the high number of participants increased the statistical power to detect effects on growth and body composition compared with previous studies 27. One other trial supplemented with a dose similar to ours from week 30 of pregnancy and completed follow-up for 243 participants at age 19 years, finding no effect on waist circumference or BMI, which could be caused by low numbers 28.…”
Section: Discussionmentioning
confidence: 59%
“…The changes in fatty-acid composition in milk might have directly influenced the concentration of these compounds in pup serum. A Recent human study suggests that breast milk fatty-acid profile related to infant growth and body composition [31]. Both maternal high-fat diet and overfeeding during the postnatal period resulted in a significant increase of bodyweight in offspring, about 20% greater than pups in the Control group.…”
Section: Discussionmentioning
confidence: 99%